Postoperative Abdominal Hemorrhage Following Pancreatoduodenectomy.: a propósito de 2 observaciones sucesivas - Praderi, Raúl; Bogliaccini, Gustavo; Estefan, Alberto; Pomi, Jorge; Castiglioni, Juan Carlos (Cirugía del Uruguay, 1981)
Report on two Sucessive Cases One of the complications which are likely to occur following pancreatoduodenectomies, is postoperatory hemorrhage, favoured by the complex anatomical dissection, the multiple sutures and coaguration disorders brought about by jaundice.